Production and Characterization of an Integrated Multi-Layer 3D Printed PLGA/GelMA Scaffold Aimed for Bile Duct Restoration and Detection - Xiang, Yang; Wang, Weijia; Gao, Yuanhui; Zhang, Jianquan; Zhang, Jing; Bai, Zhiming; Zhang, Shufang; Yang, Yijun (Frontiers in Bioengineering and Biotechnology, 2020)
We successfully fabricated artificial bile duct via 3D printing technique which was composed of poly (lactic-co-glycolic acid) (PLGA) and gelatin methacrylate (GelMA). The PLGA-inner layer provided sufficient strength to support the bile duct contraction, the GelMA-outer layer possessed good biocompatibility to provide a good living environment for the cells. Moreover, IKVAV laminin peptide (Ile-Lys-Val-Ala-Val) and ultrasmall superparamagnetic iron oxide (USPIO) were used to regulate scaffold cell adhesion and magnetic resonance imaging (MRI) detection, respectively. After BMSCs co-culture with IKVAV at a certain concentration, the survival rate and adhesion of BMSCs was increased obviously. Meanwhile, the fabricated scaffold exhibited the tensile modulus in the range of 17.19 ~ 29.05 MPa and the compressive modulus in the range of 0.042 ~ 0.066 MPa, which could meet the needs of human implantation. In an animal experiment in vivo pig bile duct regeneration, PLGA/GelMA/IKVAV/USPIO duct conduits could promote bile duct regeneration and enhance cytokeratin 19 (CK19) expression. In summary, the composite bile duct scaffold with excellent MRI imaging function and biocompatibility could be used to develop bioactive artificial bile ducts.